Genetic diversity of wild germplasm of “yerba mate” (Ilex paraguariensis St. Hil.) from Uruguay - Cascales, Jimena (2014)
The “yerba mate” tree, Ilex paraguariensis St. Hil., is a crop native to subtropical South America, marketed for the elaboration of the highly popular “mate” beverage. The Uruguayan germplasm occupies the southernmost area of the species distribution range and carries adaptations to environments that considerably differ from the current production area. We characterized the genetic variability of the germplasm from this unexplored area by jointly analyzing individuals from the diversification center (ABP, Argentina, Brazil and Paraguay) with 19 nuclear and 11 plastidic microsatellite markers. For the Uruguayan germplasm, we registered 55 alleles (18 % private), and 80 genotypes (44 % exclusive), whereas 63 alleles (28.6 % private) and 81 genotypes (42 % exclusive) were recorded for individuals from ABP. Only two plastidic haplotypes were detected. Distance-based and multilocus genotype analyses showed that individuals from ABP intermingle and that the Uruguayan germplasm is differentiated in three gene-pools. Significant positive correlations between genetic and geographic distances were detected. Our results concur in that ABP individuals harbor greater genetic variation than those from the tail of the distribution, as to the number of alleles (1.15-fold), He (1.19-fold), Rs (1.39-fold), and the between-group genetic distances (1.16-fold). Also the shape of the genetic landscape interpolation analysis suggests that the genetic variation decays southward towards the Uruguayan territory. We showed that Uruguayan germplasm hosts a combination of nuclear alleles not present in the central region, constituting a valuable breeding resource. Future conservation efforts should concentrate in collecting numerous individuals of “yerba mate” per site to gather the existent variation.